2008
DOI: 10.1088/0957-4484/19/43/435609
|View full text |Cite
|
Sign up to set email alerts
|

Preferential growth of ZnO thin films by the atomic layer deposition technique

Abstract: Preferred orientation of ZnO thin films deposited by the atomic layer deposition (ALD) technique could be manipulated by deposition temperature. In this work, diethyl zinc (DEZn) and deionized water (H(2)O) were used as a zinc source and oxygen source, respectively. The results demonstrated that (10.0) dominant ZnO thin films were grown in the temperature range of 155-220 °C. The c-axis crystal growth of these films was greatly suppressed. Adhesion of anions (such as fragments of an ethyl group) on the (00.2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
140
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(163 citation statements)
references
References 35 publications
22
140
1
Order By: Relevance
“…In agreement with our results, on Si(100) substrates, polycrystalline ZnO films with a (100) preferential orientation have been obtained by thermal ALD (using DEZ and water), 14 PE-ALD (using DEZ and O 2 -plasma), 31 and PE-ALD (using DMZ and O 2 -plasma) 35 at 130, 100, and 25 C, respectively. However, a study of thermal ALD (using DEZ and water) at 23 C yielded ZnO with a (002) preferential orientation.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with our results, on Si(100) substrates, polycrystalline ZnO films with a (100) preferential orientation have been obtained by thermal ALD (using DEZ and water), 14 PE-ALD (using DEZ and O 2 -plasma), 31 and PE-ALD (using DMZ and O 2 -plasma) 35 at 130, 100, and 25 C, respectively. However, a study of thermal ALD (using DEZ and water) at 23 C yielded ZnO with a (002) preferential orientation.…”
supporting
confidence: 91%
“…1 These properties are essential for various applications such as solar cells, 2-4 transparent conductive oxide layers, [5][6][7][8] piezoelectric nanogenerators, [9][10][11][12] and gas sensors. [13][14][15] The ability to tune optical and structural properties of the zinc oxide films is crucial for adapting the material characteristics to meet device requirements (i.e., enhanced device efficiency or sensitivity). [16][17][18] Furthermore, the application of ZnO on thermo-sensitive substrates such as polymers [19][20][21] and biomaterials 22,23 requires deposition processes operating at low temperatures which should be well below the glass transition temperature of polymers and temperatures that would lead to, e.g., degradation of the biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal orientation of ZnO films is controlled by its deposition temperature: 280 C and 165 C being used for the (0001) and (10 10) planes respectively. 85 The as-grown ZnO films were annealed at 800 C (1 hour) prior to the confirmation of crystal orientation by XRD. All substrates studied, ZnO films, silicon wafers, and glass slide, were cleaned with acetone, dried in air, and placed into 12 mL peptide solution prepared in PBS (phosphate buffered saline, 50 mM phosphate and 150 mM NaCl, pH 7.0).…”
Section: Peptide Adsorption Studiesmentioning
confidence: 99%
“…However, when the temperature is above 200 C, the DEZn molecules desorb from the c-Al 2 O 3 surface and the growth rate becomes much less than one monolayer per ALD cycle. 14) We found that when a ZnO seed layer is prepared by ALD on the c-Al 2 O 3 at T ¼ 180 C and heat-treated at a high temperature, the DEZn molecules can be absorbed on the ZnO seeds at T 200 C. This indicates that the surface of ZnO seed layer offers stable absorption sites for DEZn molecules at high growth temperatures. On the other hand, it has been pointed out that at the first 20 cycles in the ALD process, the deposition rate is much smaller than one monolayer per ALD cycle.…”
Section: Procedures For the Fabrication Of Zno Nanopillarsmentioning
confidence: 78%
“…ALD has been used only to deposit a seed layer to grow ZnO nanorods. [12][13][14] Although the nanoscaled control of film thickness is easily achieved by ALD, none have applied ALD to deposit the nanostructures.…”
Section: Introductionmentioning
confidence: 99%